Trends in Private Investment in Developing Countries : Statistics for 1970-2000 and the Impact on Private Investment of Corruption and the Quality of Public Investment - Everhart, Stephen S.; Sumlinski, Mariusz A. (Washington, DC: World Bank and the International Finance Corporation, 2013)
The report is part of the continued investigation on the public-private investment relationship, and its focus for this year is on the quality of public investment, its interaction with corruption, and the resulting impact on private investment. The first chapter provides statistics on trends in private, and public fixed investment in sixty three developing countries, with a substantially expanded sample coverage of the Eastern Europe and Central Asia Region, as well as some smaller economies of the Latin America and Caribbean Region. On average, the ratio of private investment to GDP, declined in 1999 compared to 1998, while public investment increased in simple average terms, and remained at 1998 levels in weighted average terms. The 1999 decline brings investment ratios back to their 1995 level, and, preliminary (incomplete) estimates for 2000, suggest that private investment may be poised for a return to growth. The second chapter examines whether higher levels of public investment are associated with higher, or lower levels of private investment, the impact of corruption on this relationship, and the long-run implications for growth, and sustainable development. The paper is consistent with the hypothesis that corruption lowers the quality of public investment, and that this reduced quality is associated with lower private investment.